2003
DOI: 10.1021/cm0208859
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Oligofluorenes Forming Glassy-Nematic Films for Polarized Blue Emission

Abstract: The first series of monodisperse glass-forming, nematic oligofluorenes was synthesized following a divergent−convergent approach. Both chain length and pendant structure were found to affect solid morphology and phase transition temperatures. With optimized structural parameters, a T g close to 150 °C and a T c beyond 375 °C were achieved. This material class is characterized by its ability to form monodomain glassy nematic films via spin-coating, thermal annealing at 10 to 20 °C above T g for 15−30 min, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
164
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(167 citation statements)
references
References 33 publications
2
164
1
Order By: Relevance
“…[19] As a class of photonic materials, monodisperse conjugated oligomers are characterized by a relatively short and uniform chain length, solubility and chemical purity, and ease of processing [20] with a potential for spontaneous uniaxial alignment mediated by nematic mesomorphism. Few existing conjugated oligomers are capable of forming glassy nematic films for polarized light emission with the exception of properly functionalized oligo(fluorene)s. [21] The potential of this material class has also been substantially enhanced with elevated glass transition and clearing temperatures while avoiding spontaneous crystallization normally encountered with low molecular mass organic materials. Here, we report the first polarized OLEDs using monodisperse oligo(fluorene)s on a PEDOT/PSS conductive alignment layer.…”
Section: ±1mentioning
confidence: 99%
See 1 more Smart Citation
“…[19] As a class of photonic materials, monodisperse conjugated oligomers are characterized by a relatively short and uniform chain length, solubility and chemical purity, and ease of processing [20] with a potential for spontaneous uniaxial alignment mediated by nematic mesomorphism. Few existing conjugated oligomers are capable of forming glassy nematic films for polarized light emission with the exception of properly functionalized oligo(fluorene)s. [21] The potential of this material class has also been substantially enhanced with elevated glass transition and clearing temperatures while avoiding spontaneous crystallization normally encountered with low molecular mass organic materials. Here, we report the first polarized OLEDs using monodisperse oligo(fluorene)s on a PEDOT/PSS conductive alignment layer.…”
Section: ±1mentioning
confidence: 99%
“…[21] It was found that the oligomer's chain length, pendant structure, and molecular aspect ratio affect thermotropic properties, phase transition temperatures, glass-forming ability, and absorption and photoluminescence dichroic ratios. Three promising oligo(fluorene)s were selected for an exploration of polarized OLEDs, viz.…”
Section: ±1mentioning
confidence: 99%
“…Recall that thermal annealing of these two films on rubbed polyimide alignment layers produced essentially the same S value, 0.83 for OF 16 and 0.82 for OF2T 21 annealed at 160 and 115 C, respectively, despite the difference in their molecular structures. Thermal annealing of OF and OF2T films on Polymer 1 photoalignment layers at 185 and 155 C also FIGURE 4 S of 90-nm-thick OF2T films on 10-nm-thick Polymer 1 photoalignment layers with X ¼ 0.31 as a function of exposure time to chloroform vapor at specified P r values followed by vacuum drying at room temperature for 3 h. At P r ¼ 1.00 over 1 =2 and 1 min exposure, S ¼ 0.28 and 0.00 (dewetting), respectively.…”
Section: Resultsmentioning
confidence: 93%
“…The synthesis and properties of OF, OF2T, and Polymer 1 have been reported previously; 16,21,39 Polymer 1 was characterized to have a number average molecular weight of 8,960 g mol À1 and a polydispersity index of 4.6. The polymer analog of OF2T and PF2T with a number-average molecular weight of 36,200 g mol À1 and a polydispersity index of 3.1, was used as received from American Dye Source (Quebec, Canada); its thermotropic properties have been reported earlier.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation